(untitled) (La Pediatria Medica e Chirurgica, 2012)
The first cases of atresia or web in the pyloric and prepyloric regions were described in the literature since 1937. To date, only one case of atresia at the junction between the fundus and the body of the stomach has been reported. We want to describe a complex case with incomplete atresia between fundus and gastric body, with left lateral diaphragmatic hernia, treated in several stages by endoscopic, open surgery and minimally invasive surgery